Odpowiedzi

Najlepsza Odpowiedź!
2010-03-14T08:50:22+01:00
2(x-5)+3(y-1)=-13
2x-10+3y-3 = -13
2x+3y = - 13 + 10+3
2x+3y=0

3(x-2)-2(y+1)=5
3x-6 -2y-2=5
3x-2y=5+6+2
3x-2y=13

2x+3y=0/*3
3x-2y=13/*-2

6x+9y=0
-6x+4y=-26

13y=-26/:13
y=-2

2x + 3*-2=0
2x=6 /:2
x=3

SPR.

2x+3y=0
3x-2y=13

2*3 + 3 * -2 = 0
3*3 - 2 * -2=13

6+(-6)= 0
9+4=13

6-6=0
13=13

0=0
13=13

Licze na naj
1 5 1
2010-03-14T08:51:28+01:00
2(x-5)+3(y-1)=-13
2x-10+3y-3=-13
2x+3y=-13+10+3
2x+3y=0

3(x-2)-2(y+1)=5
3x-6-2y-2=5
3x-2y=5+6+2
3x-2y=13